Neoliberalism, COVID-19 and conspiracy: pandemic management strategies and the far-right social turn. (31st May 2022) - Richards, Imogen
Abstract : Neoliberal pandemic management strategies during the 2019–2022 COVID-19 virus pandemic rendered vulnerable to the disease, people in precarious work, with underlying health issues, and experiencing other forms of social discrimination and disadvantage. Herd immunity strategies designed to address the economic growth imperatives of neoliberal societies were often contrary to scientific advice, leading to high infection rates and the mass death of, in particular, essential workers in manufacturing, healthcare, and service provision. At times, health policies and political rhetoric scapegoated marginalised communities for the spread of the disease, subjecting them to the pandemic's more harmful social and economic effects. These ideological-political environments also provided context for accelerationist and conspiratorial narratives about COVID-19 communicated among wider political networks, within economically-driven environments of counterfactual mass news and social media. Responding to this situation, this paper examines how certain pandemic responses from government and non-government actors collectively contributed toward racialised, classist social discrimination in responses to COVID-19, such that they might be said to constitute an intra-pandemic far-right 'social turn'.